Asal Permulaan Munculnya Pandangan Filsafat Sosialisme - Yanti, Yus Meri (Journal of Innovation in Teaching and Instructional Media, 2022)
Socialism is an understanding of individual ownership that is regulated and controlled collectively, not limited to individuals or just a handful of groups. The trigger for the birth of socialism is the process of the capitalist system which indirectly creates class levels in society. Socialism first emerged during the industrial revolution of the 18th century in England as a reaction to the injustices that occurred and the exploitation of workers and factory workers. Dissatisfaction and social upheaval also emerged from the socialist group which aimed to fight for the rights of oppressed factory workers. The industrial revolution made the process of producing goods easier and cheaper, thus creating the concept of capital accumulation for certain groups. This ultimately creates polarization in society, namely the employer and worker groups or the bourgeoisie or proletariat. The condition of society when capitalism developed after the industrial revolution attracted the attention of socialist thinkers such as Robert Owen in England and Saint Simon and Fourier in France. They were encouraged to improve Improving the conditions of society at that time was based on a sense of humanity without being accompanied by real actions or conceptions regarding goals and strategies in improving these conditions.